Synthesis of nanocrystalline nitrogen doped titania photocatalyst and its photodegradation properties - Yee, Ying Ying, 1991-; Lee, Siew Ling, supervisor; Fakulti Sains (2014)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2014